Pengaruh Proyek Wawancara Sejarah Lisan TerhadapHistorical Awareness dan Historical Empathy Mahasiswa - Septina Alrianingrum; Sumarno; Nasution; Fadiyah Salsabila (Keraton: Journal of History Education and Culture, 2026)
This study aims to test and analyze the influence of the oral history interview project on students' historical awareness and historical empathy. Theoretically, this study is based on Lev Vygotsky's constructivism theory which states that knowledge is constructed by individuals through interactions in their socio-cultural environment. To achieve this goal, this study uses a quantitative method with an ex post facto type. The population and sample of this study were all 127 students of the History Education study program at Surabaya State University who were selected through a saturated sampling technique. Data collection was carried out using a questionnaire instrument. The results of the data analysis indicate that there is an influence of the oral history interview project on students' historical awareness and historical empathy based on a sig value <0.05. The magnitude of this influence is indicated by the R Square value of 0.51 and 0.55 which when converted into percentage form is 51% and 55%.